Interpretive review: Semiochemicals in domestic pigs and dogs - McGlone, John J.; Archer, Courtney; Henderson, Madelyn (Frontiers in Veterinary Science, 2022)
This interpretive review includes discussion of the available scientific literature with interpretations by the authors. The broad field of semiochemicals can be confusing to scientists and consumers. This review attempts to summarize the known scientific studies for pig and dog semiochemicals while at the same time attempting to refine our use of terminology. The specific objectives of this interpretive review are to summarize and interpret much of the key scientific literature (but not the lay literature) on semiochemicals in pigs and dogs to include (1) definitions of semiochemicals and related molecules including pheromones, (2) to briefly summarize olfactory organs, and (3) and to examine the scientific literature for semiochemical mechanisms and applications in dogs and pigs (two domesticated species with known olfactory acuity). Dogs and pigs have olfactory features that are similar in that they both lack certain olfactory organs (Grueneberg ganglion and Septal Organ) and they have a small vomeronasal organ (VNO) without some major receptors that are found in other species. The primary olfactory organs for both pigs and dogs are the main olfactory epithelium and perhaps the trigeminal nerve. Several examples of pheromones activating the brain via the MOE or Trigeminal nerve rather than the VNO challenge the concept that the VNO is the site of pheromone sensing. We believe it is not appropriate to label something a pheromone when evidence is not available to show that it is a pheromone. We offer definitions for the terms semiochemicals, pheromones, interomones and others and then determine if the evidence is sufficient to call certain semiochemicals a pheromone. Here we review mixed, largely negative, scientific reports of the efficacy of some products labeled as “pheromones” that are more appropriately called semiochemicals. Interomones can have a more powerful effect on dog behavior and physiology than semiochemicals marketed as pheromones. Because marketing of semiochemicals is far ahead of the science, bringing some logic and uniformity to the field will benefit animals and hopefully cause less consumer confusion. Semiochemicals have the potential to offer powerful solutions to behavioral problems using more naturally occurring molecules.